SPD_0090 Negatively Contributes to Virulence of Streptococcus pneumoniae - Cao, Linlin; Li, Nan; Dong, Yingshan; Yang, Xiao-Yan; Liu, Jiajia; He, Qing-Yu; Ge, Ruiguang; Sun, Xuesong (Frontiers in Microbiology, 2022)
In most bacteria, iron plays an important role in the survival of bacteria and the process of infection to the host. Streptococcus pneumoniae (S. pneumoniae) evolved three iron transporters (i.e., PiaABC, PiuABC, and PitABC) responsible for the transportation of three kinds of iron (i.e., ferrichrome, hemin, and ferric ion). Our previous study showed that both mRNA and protein levels of SPD_0090 were significantly upregulated in the ΔpiuA/ΔpiaA/ΔpitA triple mutant, but its detailed biological function is unknown. In this study, we constructed spd_0090 knockout and complement strain and found that the deletion of spd_0090 hinders bacterial growth. SPD_0090 is located on the cell membrane and affects the hemin utilization ability of S. pneumoniae. The cell infection model showed that the knockout strain had stronger invasion and adhesion ability. Notably, knockout of the spd_0090 gene resulted in an enhanced infection ability of S. pneumoniae in mice by increasing the expression of virulence factors. Furthermore, iTRAQ quantitative proteomics studies showed that the knockout of spd_0090 inhibited carbon metabolism and thus suppressed bacterial growth. Our study showed that SPD_0090 negatively regulates the virulence of S. pneumoniae.